ANALISIS KEBIJAKAN PEMUNGUTAN PAJAK HOTEL ATAS RUMAH KOS DITINJAU DARI PERSPEKTIF ASAS-ASAS PEMUNGUTAN PAJAK DAERAH (Studi Pada Dinas Pendapatan Dan Pengelolaan Keuangan Kota Surabaya) - Murandika, Muhammad Friansyah (Jurnal Mahasiswa Perpajakan, 2014)
The background of this research is to determine the hotel tax over the boarding house by the city of Surabaya. This study aims to identify and analyze the tax policy of the hotel above the boarding house when viewed from the perspective of the principles of local taxation, investigate and analyze Â tax implementation on boarding houses as well as identify and analyze the factors that affect the enforcement of tax collection over the boarding house to hotel Department of Revenue and Fiscal Management in Surabaya. The research method used is descriptive qualitative method, using documentations and interviews as a data collection tool that is made to the parties who are competent and are directly related to the implementation of tax collection over the boarding house hotel in Surabaya. Analysis of the data in this study using descriptive analysis. Based on the analysis of the data obtained that the taxation policy of the hotel over a boarding house in the city of Surabaya when viewed from the perspective of the principles of local taxation has not been fully met. While the results of the analysis of the hotel tax implementation collection over the boarding house in Surabaya views of the aspects that affect the implementation of a tax indicates has met. Supporting factors that arise is competent human resource, good computer systems and facilities and adequate infrastructure. Inhibiting factors that arise are not effective regulation and low consideration from the boarding house owners. Keywords: the principles of local taxation, mplementation, and influence factors.